ACTIVITY TEST OF RED BETEL LEAF ETHANOL EXTRACT (Piper crocatum Ruiz & Pav) AS AN ACTIVE INGREDIENT IN SUNSCREEN PREPARATIONS - Siti Hindun; Nopi Rantika; Aji Najihudin; Nurul Auliasari; Winna Khoerunisa (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Skin that is continuously exposed to sunlight can cause a reduction in the structure and elasticity of the skin and other bad effects, so it is necessary to have a skin protective agent, one of which is using sunscreen preparations. In the cosmetics sector, making products from natural ingredients is more profitable. They have a good tolerance for the skin because they do not cause severe irritation to sensitive skin. This research aims to determine the activity of red betel leaf ethanol extract as a sunscreen by looking at the SPF (Sun Protection Factor) value. The determination of the SPF value of red betel leaf ethanol extract was carried out in vitro using UV-Vis spectrophotometers at a wavelength range of 290 – 320 nm. Phytochemical testing is carried out to determine the content of chemical compounds that play a role in sunscreen activity. The research results show that the SPF values obtained from concentrations of 100, 200, 300, 400, 500, and 600 ppm, respectively, are 8.486 (extra-protection), 10,849 (maximum protection), 13,709 (maximum protection), 17.1 (ultra protection), 22 (ultra protection) and 25 (ultra protection). Based on the results of phytochemical tests, the ethanol extract of red betel leaves positively contains phenolics, flavonoids, alkaloids, tannins, saponins, steroids, and/or terpenoids. Keywords: Red betel leaves (Piper crocatum Ruiz &Pav), Sunscreen, SPF, In-Vitro, Ultra-protection